2014
DOI: 10.1128/jcm.02422-13
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Outbreak of Salmonella enterica Serovar Typhimurium Primarily Affecting a Pediatric Ward in South Africa in 2012

Abstract: eWe describe a nosocomial outbreak of diarrheal disease caused by extended-spectrum ␤-lactamase-producing multidrug-resistant Salmonella enterica serovar Typhimurium, focused on a pediatric ward in South Africa. The outbreak peaked between May 2012 and July 2012. Person-to-person transmission was the most likely mechanism of spread of the infection, expedited due to a breakdown in hand-washing and hygiene, suboptimal infection control practices, overcrowding of hospital wards, and an undesirable nurse-to-patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…Third, salmonellosis is principally a food-related infection largely of community setting origin [ 18 ]. Although there have been sporadic reports of health-care related Salmonella outbreaks [ 121 ], health-care associated infections in Africa [ 122 ] have been linked with Gram-negative bacilli other than Salmonella . Moreover, in a review of surveillance data of 33188 paediatric admissions in Kenya (2002–2009), Gram-negative bacilli other than Salmonella were the major causes of hospital-acquired bacteraemeia [ 123 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, salmonellosis is principally a food-related infection largely of community setting origin [ 18 ]. Although there have been sporadic reports of health-care related Salmonella outbreaks [ 121 ], health-care associated infections in Africa [ 122 ] have been linked with Gram-negative bacilli other than Salmonella . Moreover, in a review of surveillance data of 33188 paediatric admissions in Kenya (2002–2009), Gram-negative bacilli other than Salmonella were the major causes of hospital-acquired bacteraemeia [ 123 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data on long-term care facilities were also not always forthcoming; thus, this finding may not be truly reflective, as some HIV-infected patients in particular may have acquired iNTS while in these care facilities. Nosocomial salmonellosis is well described in South Africa, often affecting children [21,22] and nonetheless warrants careful monitoring. In contrast to invasive shigellosis, [23] we did not see an excess of adult women presenting with iNTS: intrinsic characteristics of Salmonella , in HIV-infected patients in particular, appear to be at play in the context of invasive disease, beyond human behavioral factors.…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella Typhimurium ST313 is well associated with HIV [27]; we found that the organism contributes significantly to NTS meningitis in HIV-infected patients. Besides ST313, representing 67% of typed Salmonella Typhimurium isolates, ST19 represented 31% of typed isolates; ST19 is commonly described worldwide, including from South Africa [39]. A stronger association between HIV infection and Salmonella meningitis due to Salmonella Typhimurium ST313, compared with Salmonella Typhimurium ST19, was noted.…”
Section: Discussionmentioning
confidence: 99%
“…A stronger association between HIV infection and Salmonella meningitis due to Salmonella Typhimurium ST313, compared with Salmonella Typhimurium ST19, was noted. In our previous report of predominantly noninvasive Salmonella Typhimurium ST19 infection, most of the patients were HIV uninfected [39]. …”
Section: Discussionmentioning
confidence: 99%